Philip Ward, The Oxford companion to Spanish literature. Clarendon Press-Oxford University Press, Oxford, 1978; 629 pp. - Venier, Martha Elena (Nueva Revista de Filología Hispánica (NRFH), 1979)
Se reseñó el libro: The Oxford companion to Spanish literature.